Traumatic aortic injury presenting to an adult major trauma centre. (October 2019) - Bade-Boon, Jordan; Mathew, Joseph K; Fitzgerald, Mark C; Mitra, Biswadev
Introduction: Traumatic aortic injury is an uncommon condition. Timely diagnosis may enable early haemostatic resuscitation, essential to prevent worsening of the injury prior to definitive management. The aim of this study was to assess the utility of initial vital signs and presenting clinical characteristics to confirm or rule out aortic injury. Methods: A retrospective review of patients from The Alfred Trauma Registry was conducted. Patients presenting between January 2006 and July 2014 and diagnosed with aortic injury were identified. Demographics and presenting clinical characteristics were extracted. Sensitivity of individual clinical variables for the detection of aortic injury was calculated. Results: There were 77 patients identified with aortic injury, with an in-hospital mortality rate of 19.5% (95% CI: 10.6–28.3%). Of these, 68 (88.3%) patients presented after high-energy blunt mechanisms. Clinical signs and early chest X-ray findings were poorly sensitive to detect aortic injury. Patients who presented with hypotension had a greater severity of aortic injury, more commonly had associated abnormal investigation findings and were more likely to require blood products and inotropic agents (p < 0.05). However, sensitivity of initial hypotension to rule out aortic injury was 39.0% (95% CI: 28.1–49.9%). Conclusions: The diagnosis of aortic injury was uncommon in hospital. Most injuries were secondary to high-velocity road traffic crashes or high falls. Clinical signs were not adequately sensitive to be used for the exclusion of aortic injury. We recommend a high degree of clinical suspicion and liberal imaging among cases where aortic injury is possible.